Paulo Freire’s conscientização: A learner-centered and transformation-oriented teaching-learning theory - Egargo, Fernando Navidad (Animo Repository, 2024)
There is a great divide between teacher-centeredness and learner-centeredness in the teaching- learning process. The debate on “centeredness” in education seems to be an endless pendulum- like movement. Both ends are rooted on philosophical foundations and their merits/demerits have been subjects of scholarly studies. Based on the literature, there is a growing acceptance and tendencies towards the learner-centered model. There is no single model, however, in the learner- centered paradigm. The learner-centered group is composed of different models. Each model is governed by philosophical presuppositions, pedagogies, policies, and practices. Among these models are varied learner-centered systems adopted and practiced in many educational settings. Analyzing these models, however, from domains and standards central to learner-centered education, there are identifiable weaknesses and issues. This dissertation proposes Freire’s conscientização as a better alternative to the existing learner- centered models currently practiced in many educational settings. Conscientização is an educational-epistemological theory that is learner-centered and transformation-oriented. It is rooted on transformational teaching and transformational learning that takes into account the centrality of learners in the learning process. More importantly, it is a learner-centered teaching- learning method that links education to personal transformation as well as the capacity of the learner to be an active collaborator in the process of social transformation.